ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI PENAWARAN DAN PERMINTAANTENAGA KERJA DI SUMATERA BARAT - Noveda, Dirza; Aimon, Hasdi; Syofyan, Efrizal (Program Studi Magister Ilmu Ekonomi, 2015)
This studyaimed toanalyzethe effect of(1) wages, population growth, labor force participation rate(LFPR) andunemploymenton labor supplyin West Sumatra. (2) labor supplyand labor demandon wages. (3) wages, investment, economyandproductivityof thelabor demandin West Sumatra. This research isdescriptiveandassociative. While thetype of datais datadocumentary, the datasourceis asecondary dataas well asdata in the formof time seriesofthe first quarterof 2002-the fourth quarter of2012.This study uses asimultaneousequation modelanalysis toolwithTwoStagesLeastSquaredmethod(TSLS).The study concluded that (1) wages, labor force participation rate (LFPR) and unemployment have a significant effect on labor supply in West Sumatra. However, population growth has no significant effect on labor supply in West Sumatra. (2) labor supply and labor demand affect wages in West Sumatra significantly. (3) Wages, investment, economy and productivity significantly influence the demand for labor in West Sumatra. Based on these results policies can be suggested that the government was asked to increase education and training for jobs that could only be done by men. The government needs to increase investment oriented to the labor intensive (labor intensive) by simplifying the licensing process, the necessary policies can actually synchronize between the interests of employers and unions in wage setting both the minimum wage regional, provincial or district / city. Â Keywords :labor supply, labor demandand wages